Palladium release from catalytic converter materials induced by road de-icer components chloride and ferrocyanide. (April 2020) - Aruguete, Deborah M.; Wallace, Adam; Blakney, Terry; Kerr, Rose; Gerber, Galen; Ferko, Jacob
Abstract: Environmental levels of platinum group elements (PGEs) are rising due to emissions of vehicle catalytic converter (VCC) materials containing palladium, platinum and rhodium. When these PGE-containing VCC materials are exposed to soil and water, coordination complex formation with ligands present in the environment may mobilize PGEs into solution, particularly Pd. Road de-icing salt contains two ligands with high affinities for Pd 2+ : chloride (Cl − ) from NaCl and cyanide (CN − ) from ferrocyanide (Fe(CN)6 4− ) anti-caking agents. Batch leaching studies of VCC materials were conducted with solutions representative of de-icer-contaminated road runoff at pH 8 and room temperature for 48 h. Ferrocyanide (FC) concentrations of 0 μM, 1 μM, 2 μM and 10 μM were tested with background electrolyte concentrations of 0.028 M NaCl (1000 mg/L Cl − ) or 0.028 M NaClO4 . Palladium release increased with FC concentration, ranging from 0.014 ± 0.002 μM Pd without FC to 5.013 ± 0.002 μM Pd at 10 μM FC. At 0 μM, 1 μM and 2 μM FC, chloride induced further Pd release, but had no effect at 10 μM FC. PHREEQC modeling predicted that the predominant species present in equilibrium with Pd(OH)2 (s) were Pd(OH)2 0 and Pd(CN)4 2−, and that PdCl x 2−x complexes had only a minor effect on the total concentration of dissolved palladium. The effect of FC on Pd release was predicted but not the effect of Cl −, indicating possible kinetic control. Platinum was measured above limits of detection (LODs) only at 10 μM FC, and rhodium levels were below LODs, consistent with their slower complexation kinetics. Graphical abstract: Image 1 Highlights: Road de-icing salt causes catalytic converter materials to release palladium. Anti-caking agent (ferrocyanide) from de-icer has dominant effect on Pd release. Chloride combined with ferrocyanide synergistically boosts palladium release. Platinum release insignificant except at highest levels of ferrocyanide.